2021
DOI: 10.1007/s00428-021-03228-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological impact of SAMHD1 expression in mantle cell lymphoma

Abstract: SAMHD1 is a deoxynucleoside triphosphate triphosphohydrolase (dNTPase) that restricts viral replication in infected cells and limits the sensitivity to cytarabine by hydrolysing its active metabolite, as recently shown in acute myeloid leukemia. Cytarabine is an essential component in the Nordic mantle cell lymphoma protocols (MCL2 and MCL3) for induction and high-dose chemotherapy treatment before autologous stem cell transplantation for younger patients with mantle cell lymphoma (MCL). We here investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…However, the correlation was mainly driven by lower SAMHD1 expression in nonnodal MCL (nnMCL) ( supplemental Figure 10 C) and lost when restricting the analysis to cMCL ( supplemental Figure 10 B). Consistently, silencing of SOX11 in SOX11 + MCL cell lines 19 or induction of SOX11 in SOX11 − JVM-2 ( Figure 3 F; supplemental Figure 10 D) did not affect SAMHD1 expression. Analyses of SAMHD1 histone marks and DNA methylation together with SAMHD1 messenger RNA expression in 5 published MCL cases (2 cMCL and 3 nnMCL) in comparison with normal B cells 43 , 44 did not further reveal evidence of epigenetic regulation of differential SAMHD1 expression in MCL ( supplemental Figure 10 E).…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…However, the correlation was mainly driven by lower SAMHD1 expression in nonnodal MCL (nnMCL) ( supplemental Figure 10 C) and lost when restricting the analysis to cMCL ( supplemental Figure 10 B). Consistently, silencing of SOX11 in SOX11 + MCL cell lines 19 or induction of SOX11 in SOX11 − JVM-2 ( Figure 3 F; supplemental Figure 10 D) did not affect SAMHD1 expression. Analyses of SAMHD1 histone marks and DNA methylation together with SAMHD1 messenger RNA expression in 5 published MCL cases (2 cMCL and 3 nnMCL) in comparison with normal B cells 43 , 44 did not further reveal evidence of epigenetic regulation of differential SAMHD1 expression in MCL ( supplemental Figure 10 E).…”
Section: Resultssupporting
confidence: 55%
“…We have previously shown that there is a weak positive correlation of SOX11 and SAMHD1 expression based on immunohistochemistry (N = 62; Spearman correlation coefficient, 0.27; P = .036). 19 To further investigate this, we analyzed gene expression data of 44 previously published MCL cases 43 and confirmed a positive correlation of SAMHD1 and SOX11 expression (Spearman rank correlation R = 0.37; P = .013; supplemental Figure 10 A). However, the correlation was mainly driven by lower SAMHD1 expression in nonnodal MCL (nnMCL) ( supplemental Figure 10 C) and lost when restricting the analysis to cMCL ( supplemental Figure 10 B).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations